Toward adopting a skills development fund for Cambodia. (Metro Manila, Philippines Asian Development Bank, 2018)
Cambodia new technical and vocational education and training (TVET) policy aims to promote public private partnerships and mobilize resources to support TVET. A key strategy is to set up a national skills development fund.
Keywords: Education -- Cambodia; Public - private partnesrship; Electronic books